The Dreamland: Validation of a Structured Dream Diary - Holzinger, Brigitte; Mayer, Lucille; Barros, Isabel; Nierwetberg, Franziska; Klösch, Gerhard (Frontiers in Psychology, 2020)
Validated instruments for the analysis of dream contents are still scarce. Therefore, the aim of this study was to validate the Dreamland Questionnaire (DL-Q) by comparing its results to those of the Hall and van de Castle Coding System (HVDC). Twenty-two participants voluntarily filled in a written dream report as well as our DL-Q questionnaire, in total 30 dreams were collected with both measures. Written reports were analyzed with the HVDC and results of the two instruments were compared using Pearson correlations. Results showed that correlations were high for dominant characters, pleasantness of dream content, and body-related experiences. However, some DL-Q items showed low correlations and others could not be compared directly, as the HVDC did not include the same set of items. The DL-Q showed satisfactory validity and reliability as a measure of dream criteria and may serve as an effective tool for diagnosis and evaluation and facilitate future clinical and research studies. Nevertheless, some items could not be compared as part of this study and should be validated in future investigations.